2000
DOI: 10.1017/s095410200000002x
|View full text |Cite
|
Sign up to set email alerts
|

Southern elephant seal movements and Antarctic sea ice

Abstract: ObjectiveSatellite telemetry was used to investigate the migratory behaviour of southern elephant seals (Mirounga leonina). The seal studies were part of the German-Argentinean cooperation project and carried out at Stranger Point on King George Island between September 1996 and February 1997. Stranger Point (62°14'S; 58°40'W) is the southernmost breeding site of elephant seals. Elephant seals are able to dive to depths in excess of 1500 m and feed on squid and fish. The objective of this study was to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
94
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 31 publications
4
94
3
Order By: Relevance
“…Moreover, a differential response of female and male individuals to this temporal variation was observed. While satellite telemetry studies have not indicated sexual segregation in the foraging areas of juvenile males and females of this colony (Bornemann et al, 2000(Bornemann et al, ), daneri et al (2000(Bornemann et al, , 2014 reported gender differences in the cephalopod diet of the adult component of the population, with octopod prey becoming more important in males. The interannual differences observed in the composition of the diet of juveniles of M. leonina could be linked to temporal changes in the availability of prey, mainly krill (Euphausia superba) in the feeding areas.…”
Section: Lrl/lhlmentioning
confidence: 87%
See 3 more Smart Citations
“…Moreover, a differential response of female and male individuals to this temporal variation was observed. While satellite telemetry studies have not indicated sexual segregation in the foraging areas of juvenile males and females of this colony (Bornemann et al, 2000(Bornemann et al, ), daneri et al (2000(Bornemann et al, , 2014 reported gender differences in the cephalopod diet of the adult component of the population, with octopod prey becoming more important in males. The interannual differences observed in the composition of the diet of juveniles of M. leonina could be linked to temporal changes in the availability of prey, mainly krill (Euphausia superba) in the feeding areas.…”
Section: Lrl/lhlmentioning
confidence: 87%
“…Another explanation might be associated to more northerly feeding grounds of juveniles which may reach the Antarctic Polar Front or even further north. In this regard Bornemann et al (2000) reported one juvenile (underyearling) elephant seal from Isla 25 de Mayo which traversed the Drake Passage and almost reached the patagonian shelf when the satellite transmitter failed.…”
Section: Lrl/lhlmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that many of the prey species are at these depths and overlap of M. leonina with commercial surface squid jigging and shallow water trawl fisheries should be minimal while use of the current fishing gear is continued. The situation is likely to be different for each population sector as fish species and their proportions are different and the various M. leonina age classes feed in different areas (Bornemann et al 2000). In that paper, foraging locations of weaned pups from King George Island are different to those of adult females.…”
Section: Foo (%) Ibm (%)mentioning
confidence: 93%